Kedudukan Hukum Islam dalam Sistem Ketatanegaraan Indonesia - Muhammad Idris (Al-'Adl, 2008)
The Republic of Indonesia is not an Islamic State. By complying with the Jakarta Charter in the Presidential Decree of July 5, 1959, it is by no means an Islamic state in Indonesia. With the recognition of the Jakarta Charter, it can be interpreted that Islamic Law applies to the followers of Islam as well as the politics of the Dutch East Indies before 1929. The new order government imposed Islamic law for its adherents with Law No. 1 of 1974 on marriage. RUU-PA, is the implementation of Article 24 of the 1945 Constitution and Article 10 of Law No. 14 of 1970 on the basic provisions of judicial power.